Reinforced concrete design to Eurocode 2 - Mosley, Bill (Palgrave Macmillan, 2012)
The book contains many worked examples to illustrate the various aspects of design that are presented in the text. The seventh edition of the text has been fully revised and updated to reflect the interpretation and use of Eurocode 2 since its introduction. Students and practitioners, both in the UK and elsewhere in the world where Eurocode 2 has been adopted, will find it a concise guide both to the basic theory and to appropriate design procedures. Design charts, tables and formulae are included as design aids and, for ease of reference, an appendix contains a summary of important design information.